Pemanfaatan Media Pembelajaran E-Learning Dengan Menggunakan Media Sosial Edmodo Bagi Guru SMK Al-Madani Kota Pontianak - Syarifah Putri Agustini Alkadri (Universitas Muhammadiyah Pontianak, 2018)
Edmodo is one of the learning management system (LMS) platforms that make it easy for users to create groups and share ﬁles, links, video (embed videos) and pictures with alert, assignment and event events. Edmodo provides a secure and easy way to communicate and collaborate between students and teachers, sharing textual content, link images, video and audio. Community Service Activities (PKM) aims to introduce and maximize the use of E-Learning Application based on social media Edmodo to Guru SMK Al-Madani Pontianak City. The training will be held in 2 sessions where the ﬁrst session will focus on the basic introduction of Edmodo while in the second session will focus on the practice and simulation of the learning process by utilizing the features available on Edmodo. Training modules will be included in the training as a tool for participants in practical activities.